Temporal Metagenomic and Metabolomic Characterization of Fresh Perennial Ryegrass Degradation by Rumen Bacteria - Mayorga, Olga L.; Kingston-Smith, Alison H.; Kim, Eun J.; Allison, Gordon G.; Wilkinson, Toby J.; Hegarty, Matthew J.; Theodorou, Michael K.; Newbold, Charles J.; Huws, Sharon A. (Frontiers in Microbiology, 2016)
Understanding the relationship between ingested plant material and the attached microbiome is essential for developing methodologies to improve ruminant nutrient use efficiency. We have previously shown that perennial ryegrass (PRG) rumen bacterial colonisation events follow a primary (up to 4 h) and secondary (after 4 h) pattern based on the differences in diversity of the attached bacteria. In this study we investigated temporal niche specialisation of primary and secondary populations of attached rumen microbiota using metagenomic shotgun sequencing as well as monitoring changes in the plant chemistry using mid-infrared spectroscopy (FT-IR). Metagenomic Rapid Annotation using Subsystem Technology (MG-RAST) taxonomical analysis of shotgun metagenomic sequences showed that the genera Butyrivibrio, Clostridium, Eubacterium, Prevotella and Selenomonas dominated the attached microbiome irrespective of time. MG-RAST also showed that Acidaminococcus, Bacillus, Butyrivibrio and Prevotella rDNA increased in read abundance during secondary colonisation, whilst Blautia decreased in read abundance. MG-RAST Clusters of Orthologous Groups (COG) functional analysis also showed that the primary function of the attached microbiome was categorised broadly within ‘metabolism’; predominantly amino acid, carbohydrate, and lipid metabolism and transport. Most sequence read abundances (51.6, 43.8, and 50.0% of COG families pertaining to amino acid, carbohydrate and lipid metabolism, respectively) within these categories were higher in abundance during secondary colonisation. Kyoto encyclopedia of genes and genomes (KEGG) pathways analysis confirmed that the PRG- attached microbiota present at 1 and 4 h of rumen incubation possess a similar functional capacity, with only a few pathways being uniquely found in only one incubation time point only. FT-IR data for the plant residues also showed that the main changes in plant chemistry between primary and secondary colonisation was due to increased carbohydrate, amino acid and lipid metabolism. This study confirmed primary and secondary colonisation events and supported the hypothesis that functional changes occurred as a consequence of taxonomical changes. Sequences within the carbohydrate metabolism COG families contained only 3.2 % of cellulose activities, on average across both incubation times ( 1 and 4 h), suggesting that degradation of the plant cell walls may be a key rate- limiting factor in ensuring the bioavailability of intra-plant nutrients in